2020
DOI: 10.36803/ijpmr.v9i1.252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jacobson’s Progressive Muscular Relaxation on Sleep Quality in Elderly at Budi Agung Social Institution

Abstract: ABSTRACT Background: The quality of sleep in elderly tend to decline. This occurs as a result of certain changes such as physical, biological, mental and socio-economic. The quality of sleep may influence the healthcondition for short or long terms. Poor quality of sleep may cause difficulty in concentrating, slow response, memory disturbance and decrease of performance in daily life. The decline of sleep qualitymay be resolved with Jacobson’s Progressive Muscular Relaxation (JPMR) exercise. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Training programs can also teach employees to improve alertness and manage fatigue on the job. Studies have also identified the importance of exercise in neutralizing the impact of sleep problems among employees (Kareri et al, 2020; Lederman et al, 2019). Organizations and managers can therefore motivate their employees to engage in physical exercise at home or even at the office.…”
Section: Discussionmentioning
confidence: 99%
“…Training programs can also teach employees to improve alertness and manage fatigue on the job. Studies have also identified the importance of exercise in neutralizing the impact of sleep problems among employees (Kareri et al, 2020; Lederman et al, 2019). Organizations and managers can therefore motivate their employees to engage in physical exercise at home or even at the office.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian oleh Kareri, Manafe, dan Payong menunjukkan bahwa pemberian PMR meningkatkan kepuasan subjek terhadap kualitas tidur sebesar 73,68%, dengan persentase subjek yang mengalami kualitas tidur baik meningkat menjadi 78,95%. 20 Terapi slow stroke back massage dapat memengaruhi sistem saraf parasimpatis, menginduksi sensasi relaksasi, dan menyebabkan peningkatan hormon endorfin sambil mengurangi kortisol. Hal ini berkontribusi pada stabilitas emosional dan peningkatan kualitas tidur.…”
Section: Hubungan Kualitas Tidur Dengan Fungsi Kognitifunclassified
“…Jacobson's progressive muscular relaxation works on the basis of first tensing the muscles, then relaxing them. Peace of mind and emotional equilibrium can be obtained by relaxation (14) . Jacobson's relaxation has become an essential part of care for patients with chronic diseases due to its various benefits, which include alleviating anxiety and tension, focusing attention away from pain, releasing tense and spasming muscles, encouraging sleep, and decreasing fatigue level (15) .…”
Section: Jacobsonmentioning
confidence: 99%
“…A purposive sample of 61  Have any debilitating diseases as heart failure and cancer that may impede the prognosis. Sample size Calculation: Sample size was calculated for the paired sample (before-after study) using MedCalc software version 22.009 based on the following parameters: proportion of good sleep quality of geriatric pre/post Jacobson intervention"31.58%; 84.21% respectively" (14) with Type I error /Alpha=0.0.5 and Power = 99%, the beta error was 0.01, the calculated sample size was found to be 56; adding a 10% expected nonresponsive rate, the sample size was 61 cases were recruited to the study.…”
Section: Study Subjectsmentioning
confidence: 99%